ANALYZING GENDER GAPS IN ORGANIZATIONAL DESIGN – CASE STUDY: IT SECTOR IN INDIA - Srinivasan, Uma (Digital Repository of Theses - SSBM Geneva, 2023)
It is a known fact that women are inherently viewed as home makers with the core responsibility of rearing children and taking care of homes and families. With industrial revolution, the last couple of decades have seen a seismic shift in the role of women in the society. Women have paved their way into active workforce over the last five decades or so in developed nations and for about three decades in developing nations. This relatively delayed entry into active workforce has seeded in differences in the way women are treated at work and while women are rubbing shoulder to shoulder there in an inherent gap—called the gender gap. The purpose of this study is to explore the genesis of this gap and how it manifests itself across organizations in various processes. This article aims to funnel down the gender gap and gender pay gap to the IT industry in India and corelate it to organization design, impact to organizations and contribution of women themselves to creating this gap.